THE CONCEPT OF CHILDREN'S EDUCATION IN THE PERSPECTIVE OF IBN SINA - Fauqotus Silfya; Nasikhin; Fihris (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
Children's education is an effort to develop the potential that each individual has from an early age. Through education, children not only understand knowledge but are also able to express and apply it in facing various life problems. The success of education requires a structured and methodological conceptual framework. This study aims to analyze the concept of children's education from Ibn Sina's perspective, focusing on three main aspects: its framework of thought, the methods applied, and its relevance to contemporary children's education.   Ibn Sina, as one of the classical Muslim thinkers, offered a holistic concept of education, covering intellectual, moral, and physical aspects. This study examines the conceptual framework, including the educational objectives, theoretical foundations, and learning methods that he proposes. In addition, this research also explores how Ibn Sina's perspective can be relevant to the concept of children's education in the modern era.   The research method used is library research, by collecting and analyzing data from various literature such as books, scientific articles, and related reference sources. The results of the study show that Ibn Sina's thoughts on children's education emphasize the balance between the development of intellect, morals, and practical skills. The contribution of this research lies in the effort to connect the legacy of classical Islamic thought with the needs of today's education, as well as providing a conceptual alternative for the development of a more integrative and characterful children's education system.